KEABSAHAN PERLAWANANPIHAK KETIGA TERHADAP SITA EKSEKUTORIAL DAN AKIBAT HUKUMNYA DI PENGADILAN NEGERI SAMARINDA - Andi Andi (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTIn the resistance against the confiscation good third party was brought against confiscation eksekutorial, nor against confiscation, such third parties fighting, and was originally called the plaintiff and the defendant challenged sequester originally called challenged consumed. Article 195 (6 and 7) HIR set: Resistance to seizure executorial; Submitted by the challenged / consumed; Submitted by third parties on the basis of property rights; Resistance filed with the district court chairman yangmelaksanakan execution; There is an obligation of the chairman of the district court that checks / cut resistance to report on the examination / decision of the case of resistance to the chairman of the district court which ordered eksekusi.Pasal 207 and Article 208 HIR set: How to apply resistance (orally or in writing); To whom / which the chairman of the district court, the resistance must be filed; The existence of the principle, that the opposition does not suspend execution; Exceptions to these principles; The possibility to apply banding.Dari clauses in question seems clear that the opposition filed against the confiscation eksekutorial. It means, that the goods in question, is the confiscation of goods that can be raised against him beg, they are in foreclosure, in other words, that the goods have not been auctioned off or must be delivered (carried surrender to the winning side).Keywords: eksekutorial seizure resistance.